A model for risk analysis in the process of building a knowledge cluster in Colombia (2011)
In such a competitive world, where companies face new challenges every day, clusters, defined as strategies that dynamize national, regional or world economic growth, have become a space leading to knowledge creation, ownership, transferring and diffusion inside companies. This strategy represents a growing source for companies and cities as much as they allow companies belonging to a common sector group into business networks, also, they can spot new business opportunities and become more competitive and sustainable. Knowledge clusters involve different agents from diverse nature such as governmental, private, industrial, educational or entrepreneurial. In other words, these represent a space where demandants (companies) and knowledge offerors (universities, research institutes, consulting groups, etc) interact.These clusters' main goal is to support knowledge creation, ownership, and application processes which can lead to a better development of competitiveness among companies by means of creating a dynamic exchange of information among the companies belonging to the cluster. This paper aims at presenting a model for risk analysis in the process of building a knowledge cluster between private companies and high education institutions (IES*) from a qualitative point of view. This methodology has been used in a process of building a knowledge cluster in Colombia.